Pre-tertiary hospital management of neoplastic neck lumps in adults: the need for an appraisal in North Western Nigeria - Mohammed, Abdullahi; Iseh, Kufre R.; Amutta, Stanley B.; Daniel, Aliyu (International Surgery Journal, 2019)
Background: Pathologies in the head and neck sites may manifest as neck lumps, which is an important prognostic significance in the management. The aim of the study was to describe the pre-tertiary hospital management of adult patients with neoplastic neck lumps. Methods: This was a retrospective study of all the patients managed for neoplastic neck lumps from September 2008 to September 2018, at the Department of Otorhinolaryngology, Usmanu Danfodiyo University Teaching Hospital, Sokoto, Nigeria. Results: A total of 118 patients were included in the study. The age ranged from 16-83 years (mean age; 42.3±16.7 years). Majority of the patients 71 (60.2%) were of lower socioeconomic status. Duration of neck swellings was between 3-240 months with an overall mean duration of 30.2 months (mean duration for benign and malignant neck masses respectively; 100±56 and 20.1±47.1 months). Malignant neck lumps 103 (87.3%) constituted most of the neck lumps, and of these, 91 (77.1%) were metastatic neck lumps. Patients delay 94 (79.7%), and professionals delay 24 (20.3%) were responsible for advanced primary head and neck neoplasia and their metastatic deposits. Eighty-seven (73.7%) patients were managed at the tertiary hospital: fifty-two (59.8%) were successfully discharged and were lost to follow up within six months after the intervention. Thirty-five (40.2%) patients died during treatment and 31 (26.3%) signed against medical advice. Conclusions: Malignant lumps, mainly the metastatic neck disease, are common in adults. The notable contributory factors for delay presentation can be preventable through creating public awareness and the improvement of socioeconomic status.